Numerical Simulation of Magnetic Dipole Flow Over a Stretching Sheet in the Presence of Non-Uniform Heat Source/Sink - Souayeh, Basma; Yasin, Essam; Alam, Mir Waqas; Hussain, Syed Ghazanfar (Frontiers in Energy Research, 2021)
Nanofluids have been defined as prominent heat transfer fluids due to their improved properties. The enhanced rheological and thermo-properties make them very useful for the solar energy applications. Hence, the current paper examines the momentum and heat transference characteristics of Maxwell nanofluid flow over a stretching sheet. Further, magnetic dipole, non-uniform heat source/sink and chemical reaction effects are considered in the modelling. By using well known similarity transformation formulated flow equations are modelled into OD equations. Numerical solutions of the governing flow equations are attained by utilizing the shooting method consolidated with the fourth-order Runge-Kutta scheme. Graphical results are deliberated and scrutinized for the consequence of different parameters on fluid characteristics. The features of heat transfer rate, surface drag force and rate of mass transfer are elaborated in detail. Results reveal that, Radial velocity upsurges with an increment in Maxwell parameter whereas it declines for escalation of β. Temperature profile accelerates for diverse values of space dependent parameter but it shows opposite behaviour for escalated integrity of temperature dependent parameter and concentration profile upsurges for augmentation of Schmidt number and reaction rate parameter.